Gynogenesis in the spotted catfish Pimelodus maculatus using heterologous gametes from the yellowtail-tetra (Astyanax altiparanae): a key point to achieve monosex female populations in Neotropical catfishes - Bertolini, Rafaela Manchin [UNESP] (2025)
Monosex populations in aquaculture is important to increase performance for subsequent food supply. Gynogenesis is the main tool to achieve monosex population within only one generation, since it provides only maternal inheritance. The present study aimed to achieve gynogenetic individuals of spotted catfish (Pimelodus maculatus), an important Neotropical species in which the female presents better growth performance. Sperm of yellowtail-tetra (Astyanax altiparanae) was UV-irradiated (80 mJ/cm2) in order to inactivate paternal genome. Afterwards, oocytes of P. maculatus were fertilized with the irradiated sperm and heat-shocked (38 °C for 2 min, 2 mpf) for diploidization by prevention of the release of the 2nd polar body. Diploid progenies derived from P. maculatus couples served as controls, and a non-treated haploid was also produced. Flow cytometric analysis and chromosome number obtained by cytogenetic analysis confirmed that gynogenetic individuals had the same number of chromosomes as the control group, indicating that sperm inactivation and diploidization was successful. Genotyping by microsatellite markers confirmed the maternal inheritance in these gynogenetics. Macroscopic visualization of the gonads revealed an increased number of females (n = 48) and only two males, suggesting a homogametic sex determination system (XX/XY). Finally, an efficient protocol for inducing meiotic gynogenesis in P. maculatus was established using irradiated sperm from A. altiparanae. This protocol can apply to produce monosex population and clonal lines in the P. maculatus species and can contribute for future studies in basic and applied sciences.